Heat transfer evaluation of a micro heat exchanger cooling with spherical carbon-acetone nanofluid. (March 2020) - Li, Z.X.; Khaled, Usama; Al-Rashed, Abdullah A.A.A.; Goodarzi, Marjan; Sarafraz, M.M.; Meer, Rashed
Highlights: Convection of a micro-channel heat sink cooling with carbon-acetone nanofluid studied experimentally. Heat transfer coefficient, friction factor, pressure drop value, and the thermo-hydraulic performance was quantified. The structure and morphology of the nanoparticles (NPs) were characterized. The value of PD was augmented by 18.3% at Reynolds number of 1400 at wt.% = 0.1. The THP value was increased by 76% despite an increase in the PD of the system. Abstract: In this article, we experimentally measured the convective heat transfer of a micro-channel heat sink cooling with carbon-acetone nanofluid (NF), which potentially is a cost-effective nano-suspension with plausible heat transfer characteristics. The heat transfer and fluid flow characteristics including heat transfer coefficient (HTC), friction factor (FF), pressure drop value (PD), and the thermo-hydraulic performance (THP) was quantified. The structure and morphology of the nanoparticles (NPs) were characterised. It was found that carbon-acetone NF can enhance the HTC value by 73%. Also, a small increase in the FF and PD values were reported due to the augmentation of particle-fluid friction forces and viscosity. The value of PD was augmented by 18.3% at Re 1400 at wt.% = 0.1. The THP value was increased by 69% despite an increase in the PD of the system. It was identified that the promotion of heat transfer was due to the micro-scale phenomena such as Brownian motion and thermophoresis. Also, reduction in the thermal boundary layer inside the micro-channel further contributed to the promotion of heat transfer within the micro-channel.